2011
DOI: 10.1103/physrevc.84.064307
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic study of new data for extremeαdecays

Abstract: Recently discovered α decays with new or improved data, covering naturally occurring α emitters with long lifetimes, short-lived ones approaching the proton drip line, and decays of heavy and superheavy elements, have been studied in a systematic investigation within the modified two-potential approach for deformed nuclei by constructing the microscopic double-folding potential. It is found that the experimental half-lives are well reproduced in the density-dependent cluster model. Some predictions on natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…The electron pumping experiments have been performed in various semiconductor-based nanoscale devices [2][3][4]. More recently, the topological charge pump was realized in ultracold atoms in optical superlattices [5][6][7], and it was also extensively studied in theory [8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…The electron pumping experiments have been performed in various semiconductor-based nanoscale devices [2][3][4]. More recently, the topological charge pump was realized in ultracold atoms in optical superlattices [5][6][7], and it was also extensively studied in theory [8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…It should be indicated that the present calculations focus on spherical proton emitters, in order to pursue a unified framework with the calculations of cluster radioactivity. In fact, the accumulation of experimental data on spherical proton emitters appears to be more in contrast with that for deformed ones, and it is also straightforward to involve the deformation effect in the investigation [26,27]. We would like to consider this study as a first attempt and process the extension to the deformed case in our following work.…”
Section: Introductionmentioning
confidence: 91%
“…[19,27,29] and references therein). One then numerically solves the Schrödinger equation within U (r) to obtain the bound-state wave function, where the depth of the nuclear potential, λ, is determined for each decay to make the bound state characterized by the measured decay energy Q and the Wildermuth condition [19,30].…”
Section: Theoretical Frameworkmentioning
confidence: 97%
See 2 more Smart Citations